Hybrid Learning 5th International Conference, ICHL 2012, Guangzhou, China, August 13-15, 2012. Proceedings - Cheung, Simon K. S.; Fong, Joseph; Kwok, Lam-For.; Li, Kedong; Kwan, Reggie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 5th International Conference on Hybrid Learning, ICHL 2012, held in Guangzhou, China, in August 2012. The 32 contributions presented in this volume were carefully reviewed and selected from numerous submissions. In addition two keynote talks are included in this book. The topics covered are computer supported collaborative learning, experiences in hybrid learning, electronic learning, pedagogical and psychological issues, hybrid learning systems, and organizational frameworks for hybrid learning.
Keywords: Computer science; Information storage and retrieval systems; Information systems; Education; Computer Science; Computers and Education; User Interfaces and Human Computer Interaction; Computers and Society; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computer Appl. in Administrative Data Processing